PENGETAHUAN DAN PERILAKU SEKSUAL PRANIKAH REMAJA - Alfiah Rahmawati; Friska Realita (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2017)
The issue of sexuality has always been a hot topic among teenagers associated with the development of sexual behavior. Adolescents often have an insatiable curiosity about sexual matters and forced the teen to seek access toinformation through magazines, books, and movies that present the pornography and porno-action that would eventually lead to things undesirable. The purpose of this study to determine the effect of knowledge on premarital sexual behavior in adolescents.This study is a kind of descriptive analytical study using cross sectional approach. Collecting data using questionnaires, the respondents were 70 people with a probability sampling technique. The data obtained were processed statistically using the chi square.Based on the analysis obtained from 70 respondents in this study showed that (x2) = 3,702 while the calculation table (x2) with a significant level of 0.05 should be obtained (x2) = 5,9915 and the value of sig p = 0.157, which means p> 0.05. Ha then rejected and that means there is no correlation between knowledge of the behavior. There is no the relationship of knowledge between premarital sexual behavior in adolescents (pvalue> 0.05)